Salsa, sauce, and other ingredients: nature, evolution and conservation of cultural heritage - Garrido Pérez, Edgardo (2014)
All cultural manifestations of the world including food and music derived from the cultural practices developed by the first Homo sapiens who inhabited the Earth. But, how does cultural diversification occur? What makes cultural manifestations to increase, spread, or decline and how to decide payments for avoiding such decline? How to detect whether a product is a cultural heritage to be protected and not a mere fashion or creation of single individuals? Here we propose a general theory on the nature of cultural heritage by answering these questions for Afro-Caribbean music and culinary art borrowing skills from Ecology and Evolution which are sciences trying to define and protect another valuable heritage namely biodiversity. Instead of extrapolating a theory from single case studies, we coherently join more than 80 cases along one single theory. Six characteristics and principles of the theory are derived from the fact that cultural heritage is inherited from one generation to the next. (1) Conservative reproduction, (2) within generation-variability, (3) transformation throughout time, (4) exposure to forces causing trends to proliferation- and decline, (5) exposure to forces tending to territorial expansion- and reduction, and (6) rise of new culture from previous ones. We provide examples on how new cultural heritage can arise from previous ones by means of: (a) exchange with other cultural heritage, (b) sudden innovation by creative individuals, and (c) geographically mediated differentiation. Invents made by single individuals or families and being non-inherited from previous generations are not heritage so should be protected under other denominations. Cultural manifestations suffering a decline in practitioners throughout generations need to be protected by means of legal, technical, educational, and even marketing practices gaining acceptance in the new generations who are to be considered as the key for saving any heritage.